Features of correction of metabolic disorders in women with polycystic ovary syndrome - O.V. Bulavenko; D.G. Konkov; O.A. Taran; O.V. Furman; V.V. Klivak (Репродуктивная эндокринология)
Background. A significant proportion of couples worldwide suffer from infertility associated with polycystic ovary syndrome (PCOS). PCOS is characterized by increased androgen synthesis in the theca cells of the ovaries, hyperandrogenemia and ovarian dysfunction in women. Most of the clinical symptoms and altered levels of blood biomarkers in PCOS patients point to metabolic dysregulation and adaptive changes as key underlying mechanisms of disease development. Since the liver is the metabolic center of the body and participates in steroid-hormonal detoxification, pathological changes in it can contribute to endocrine disorders through the liver-ovary axis. Of particular interest is hyperglycemia, changes in secretory proteins of the liver and insulin sensitivity, which affect the maturation of ovarian follicles and can potentially lead to female infertility. Objective of the review: to provide an understanding of the new metabolic mechanisms underlying PCOS, which lead to the disease and its exacerbation, as well as to summarize therapeutic approaches to the correction of PCOS complications, in particular, liver function disorders using the drug Hepatomunil. Analysis of literary data. This review presents the relationship and underlying mechanistic basis between PCOS and metabolic disorders in women by summarizing the main pathologic features of the disease. Most symptoms of PCOS are associated with insulin resistance, type II diabetes, decreased levels of sex hormone-binding globulin, increased levels of alanine aminotransferase and aspartate aminotransferase, which may indicate liver dysfunction. The metabolic profile and function of the ovaries can be affected by any pathological changes in the levels of systemic metabolism and/or in peripheral organs, in particular the liver, which serves as the metabolic center of the body, mediating its effects through the liver-ovary axis. Conclusions. Despite the lack of a clear protocol for the correction of liver function disorders and non-alcoholic fatty liver disease in PCOS patients, lifestyle modification should be the basis. Drugs that improve metabolism, as well as hepatoprotectors with immunomodulatory properties (the drug Hepatomunil) may have positive prospects for use.